FOXP3, IL-35, and PD-L1 in intra- and peritumoral lymphocytic infiltrate of cutaneous melanomas as an important part of antitumor immunity - Zidlik, Vladimir; Hurnik, Pavel; Vantuchova, Yvetta; Michalcova, Simona; Skarda, Jozef; Hulinova, Tereza; Purova, Dana; Ehrmann, Jiri (Biomedical papers, 2025)
Background. The tumor microenvironment is a significant mediator enabling tumor growth and progression. Tumor-infiltrating lymphocytes (TILs) are an important component of this but tumor cells develop mechanisms by which they can escape the action of the immune system. Immunosuppressive mechanisms cooperate with each other and involve cells of the immune system, the tumor microenvironment itself, chemokines and cytokines. In this study, we examined the FOXP3+, IL-35+, and PD-L1+ lymphocytes in tumor tissues as they are contributing to immunosuppression in some tumors, including melanoma. Such cells are also associated with tumor progression, early metastasis, and prognosis.Methods and Results. In this study, 95 cutaneous melanomas and 25 melanocytic nevi as a control group were examined by immunohistochemistry for FOXP3+, IL-35+, and PD-L1+ lymphocytes. Melanomas were divided into four groups according to the TNM classification: pT1 (35), pT2 (21), pT3 (21), and pT4 (18). PD-L1+ lymphocytes were enriched in pT3- and pT4-stage melanomas, especially in the periphery of the lesions (P<0.001). The number of FOXP3+ lymphocytes was positively correlated with the stage of the disease, especially in the center of the tumors (P<0.001). Likewise, IL-35+ lymphocytes (P<0.001) were enriched with the stage of the tumor.Conclusion. This article demonstrates that the immunosuppressive environment develops in proportion to the stage of the melanoma. The most significant changes are found at the tumor periphery, confirming the heterogeneity of the tumor stroma which is more pronounced in more advanced tumors and which may contribute to the greater aggressiveness in these peripheral zones.
Keywords: cutaneous melanoma; tumor microenvironment; tumor-infiltrating lymphocytes; immunosuppression; immune checkpoints